Executive training in the Philippines - Manalo, Placido M. Jr (Philippine Journal of Public Administration, 1985)
Although it is difficult to assess the performance of major executive training institutions in the Philippines, there is a development orientation bias as far as the curriculum content of the various programs are concerned. Still, there is need to develop a stronger partnership between clientele and training institutions, and closer inter-institutional collaboration for executive development.